KOMUNIKASI POLITIK DAN KETERWAKILAN PEREMPUAN DALAM ARENA POLITIK - Susri Adeni; Machyudin Agung Harahap (Universitas Muhammadiyah Jakarta, 2018)
Women also become part of political activities. Unfortunately the representation of women has not been heard fully in the public space. Many women's voices have not been conveyed. This article describes the general picture of women and communication in the political arena in Indonesia. Various cases from various studies show that communication and the role of women have not been significant in the political or legislative scene. Male dominance becomes an inseparable part because of the strongly embedded culture of patriarchy in Indonesia. But women do not stop fighting for her voice. Dedication of women seen in some areas by making women as leaders. It shows women's progress and her desire to move forward and can be a representation of other women aspirations.Keywords: gender, political communication, women, politic